SUSTAINABLE INVESTMENTS AND FINANCIAL PERFORMANCE BALANCING PROFITS WITH PURPOSE - Bago, Fitra Andayani Mentari; Octafian, Ray (Penelitian dan Pengembangan Ilmu, 2025)
Sustainable investing is increasingly sought after by global investors, but the main challenge is identifying indicators that are able to balance financial returns and social/environmental goals. This research aims to analyze the main indicators of sustainable investment success using a systematic literature review approach to selected literature from 2010 to 2024. The results show that financial performance indicators, ESG criteria, and social and environmental impacts are key factors in measuring the success of sustainable investment. These findings contribute to the development of investment strategies that are more holistic and have a positive impact in the long term.